Factors affecting academic administrators’ job involvement in Malaysian universities / Nor Suhana Ahmad, Nurita Juhdi and Rodrigue Ancelot Harvey Fontaine - Ahmad, Nor Suhana; Juhdi, Nurita; Fontaine, Rodrigue Ancelot Harvey (Universiti Teknologi MARA, Perlis, 2025)
Academicians are the backbone of a university. In fact, the responsibility is even greater, specifically for the academic administrators. Though, administrative positions are not always greeted by the academicians, yet their key roles in university execution are very crucial. Majority of them considered having a dual role as highly challenging and burdensome. The aim of this research is to understand the job involvement of academic administrators. This study investigated few factors namely work overload, role conflict, rewards, autonomy and career aspiration that have an impact on the job involvement among academic administrators in Malaysian universities. In total, 325 academic administrators in Malaysia including both public and private universities participated in this study. This is basically a cross-sectional study that utilises quantitative approaches and statistical analyses. Data analysis revealed that all factors were significantly affecting the job involvement of academic administrators. Knowledge earned from this study is beneficial for the university management to have a better comprehension on the impact of these factors on the academic administrators’ job involvement